CRITIQUE OF SEROLOGICAL AND ELECTROPHORETIC STUDIES ON THE INDIAN OIL SARDINE AND MACKEREL - George, Mangaly K (Indian Journal of Fisheries, 2011)
A method found to have been applied of late for fish population studiesis the use of electrophoretic, biochemical and serological techniques in the identificationof genetic stock as the natural units of fish resources (deLigny 1969, 1971,Eckroat 1973, Iwata 1973, Mangaly and Jamieson 1978 and Grant and Utter1980). The common goal of these investigations is to describe the genetic compositionof the sample population in terms of observed gene frequencies or genotypeproportions. A standard procedure followed in all these studies involvesdetection of one or more suitable gene-marker in the form of electrophoreticvariants or serological polymorphs, calculation of gene-frequencies or genotypeproportions in the tested samples containing statistically sufficient number ofspecimens, comparison of the observed distribution pattern of different phenotypeswith that expected pattern calculated, on the basis of a proposed geneticmodel, and interpretation of significant gene-frequency differences or zygotic proportionsat one or more loci as indicative of heterogeniety of populations tested.Jamieson (1974) has focussed high-lights on these points.